(untitled) (Transport systems and technologies, 2023)
The article discusses the problems of using intelligent multi-agent systems in solving a set of problems in managing and planning processes in a modern city. The concept of constructing intelligent multi-agent systems in systems that support the concept of a Smart City based on ontological modeling is considered. The proposed approach makes it possible to build formalized ontological models and flexibly configure an intelligent multi-agent system to solve problems of coordinating the work of all services of a modern city. The transition from a city in the usual sense to a Smart City is extremely necessary due to the huge gap between the increased complexity of the political, social and economic environment of modern settlements and the already outdated administrative and technological infrastructure, unable to function effectively in the new conditions. The article shows the need to rethink the key elements and general concept of the Smart City. The definition of a Smart City as a multiagent intelligent system is presented. An ontological approach is described, which involves minimal interference in the work of city services, ensures smooth changes and can be carried out by several teams of specialists in parallel. Currently, the method is used by the authors in a project aimed at developing Smart City – a digital ecosystem of services that allows achieving a synergistic effect between various subsystems (transport, ecology, energy, urban design, etc.).